An improved two-step method based on Kriging model for beam structures. Issue 3 (December 2019) - Fengle, Xie; Zhansi, Jiang; Jiawei, Xiang; Shuilong, He
An improved two-step method for multiple cracks detection in beam structures is presented in this paper. First, the crack locations are identified by the mode shape curvatures. Second, samples of varying crack depths at the crack locations and corresponding natural frequencies are used to construct the initial Kriging model in place of the crack detection database. Finally, a particle swarm optimization algorithm is employed to detect the crack depths and update the Kriging model by an optimal point adding process. The numerical simulation and experimental verification of a cantilever beam with two cracks demonstrate that the proposed method is effective. The detection results indicate that the Kriging model can effectively reduce computation time with a similar accuracy. The detection results also indicate that the more natural frequencies used, the higher accuracy of crack depths detected.